2022
DOI: 10.1007/s12666-022-02597-3
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Microstructure, Physical and Mechanical Properties of Al Matrix Reinforced with Bi-Modal Particles Coated with Either Ni or Cu

Abstract: Powder metallurgy was used to fabricate Al/(SiC-Y2O3)/Ag/Cu or Ni nanocomposite. The ratio of SiC to Y2O3 was 50:50. SiC-Y2O3 particles were coated with 10 wt% nano-Ag, followed by coating with another layer of 10% nano-Ni or nano-Cu by an electroless chemical deposition technique. All samples were compacted by a uniaxial press under 480 MPa and then sintered in a vacuum furnace at 600 °C for 1 h holding time. Coated samples with nano-Cu have the highest densification values. The microstructure of nano-Cu-coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In addition, it can be concluded that the hardness measurements of the Al-matrix and their hybrid composites are compatible with the near-full densification properties for the produced hybrid nanocomposites Fig. (7). The presence of a ceramic material such as h-BN with its high hardness and good distribution with a good adhesion with the Al matrix particles helps in improving the total hardness of the final prepared nano composites.…”
Section: Hardness Of the Al-cnts/h-bn Hybrid Compositessupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, it can be concluded that the hardness measurements of the Al-matrix and their hybrid composites are compatible with the near-full densification properties for the produced hybrid nanocomposites Fig. (7). The presence of a ceramic material such as h-BN with its high hardness and good distribution with a good adhesion with the Al matrix particles helps in improving the total hardness of the final prepared nano composites.…”
Section: Hardness Of the Al-cnts/h-bn Hybrid Compositessupporting
confidence: 62%
“…Incorporating nanoparticles, such as CNTs, graphene, or ceramic nanoparticles, into a metal matrix can significantly enhance the mechanical properties of the resulting HMMNCs. This includes improved strength, stiffness, hardness, and wear resistance [2,6,7]. HMMNCs exhibit enhanced thermal conductivity and stability, making them suitable for applications that involve high-temperature environments, such as aerospace and automotive components.…”
Section: Introductionmentioning
confidence: 99%